2010
DOI: 10.1115/1.4000549
|View full text |Cite
|
Sign up to set email alerts
|

High Rotation Number Effects on Heat Transfer in a Rectangular (AR=2:1) Two-Pass Channel

Abstract: This paper experimentally investigated the rotational effects on heat transfer in a smooth two-pass rectangular channel (AR=2:1), which is applicable to the cooling passages in the midportion of the gas turbine blade. The test channel has radially outward flow in the first passage and radially inward flow in the second passage after a 180 deg sharp turn. In the first passage, the flow is developing and heat transfer is increased compared with the fully developed case. Rotation slightly reduces the heat transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The suggested explanation referred to the weaken effect of buoyancy and Coriolis forces which affected the local heat transfer coefficient. Huh et al [17] (Ro 6 0.45) showed that regional averaged Nusselt number ratios are affected by variations of buoyancy number in the same approximate qualitative manner as the rotation number changes. They concluded that Nu ratios increase with buoyancy number on the pressure side and decrease with buoyancy number on the suction side in the radially outward flow.…”
Section: Effects Of Wall-temperature Ratiomentioning
confidence: 96%
“…The suggested explanation referred to the weaken effect of buoyancy and Coriolis forces which affected the local heat transfer coefficient. Huh et al [17] (Ro 6 0.45) showed that regional averaged Nusselt number ratios are affected by variations of buoyancy number in the same approximate qualitative manner as the rotation number changes. They concluded that Nu ratios increase with buoyancy number on the pressure side and decrease with buoyancy number on the suction side in the radially outward flow.…”
Section: Effects Of Wall-temperature Ratiomentioning
confidence: 96%
“…And thus, the rotation effect on heat transfer diminished and the heat transfer difference between leading and trailing surface was reduced. In 2009 and 2010, Huh et al [8,9] [10] studied effect of channel aspect ratio on heat transfer for a 2:1, two-pass channel. Compared with square channel, heat transfer in 2:1 channel decreased on the leading surface while increased on the trailing surface in the first radially outward passage, and the opposite occurred in the second radially inward passage.…”
Section: Effect Of Geometrical Factorsmentioning
confidence: 99%
“…And they also included that the effect of entrance weakens as rotation number increases. Huh et al (2009) [8] investigated a sudden expansion from a circular tube to the rectangular cross section of the channel. They pointed out heat transfer is dominated by the entrance until the large Buoyancy number.…”
Section: Channel Entrance Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow separation on the leading wall was observed and explained. Huh et al [6] studied the rotation effect on heat transfer in a two-pass smooth rectangular channel (AR = 2:1) with developing flow in radial outward direction in the first passage. The rotation number varied from 0.0 to 0.45.…”
Section: Rotation Number Effectmentioning
confidence: 99%